(untitled) (Impact: Journal of Transformation, 2019)
Every electioneering period in Kenya witnesses ethnic animosity that is fuelled by hate speeches by protagonists. Language is used as a tool that evokes bitterness and thereby injuring one’s emotions leading to conflict. This has polarized this country politically. Besides understanding hate speech, this paper looks at ways in which language can be used as a tool for peace-building and enhancing national coherence. This paper borrows greatly from Cognitive Grammar as advanced by Langacker (2008). I have intentionally employed Langacker’s thoughts of Schematization, Conceptualization, Categorization, Domains, Base and Profile among others. If a linguistic item (for instance a word) can arouse ethnic animosity, is there a way in which we can achieve a less offensive conceptualization of that word? Key to this paper is that meaning is viewed as grounded in embodied human experiences and that it resides in the mind of the language users as conceptualization. Conceptualization is an interactive process between the language users. During this interaction, interpretation of meaning will depend on the knowledge of the notion at hand.